The CORRELATION BETWEEN LISTENING STRATEGIES UTILIZED BY UNIVERSITY STUDENTS IN LISTENING CLASS AND STUDENTS LISTENING COMPREHENSION : A STUDY OF ENGLISH DEPARTMENT STUDENTS AT ENGLISH STUDY PROGRAM OF MULAWARMAN UNIVERSITY - Muhammad Serghei Valentino; Iwan Setiawan; Desy Rusmawaty (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2025)
Valentino, Muhammad Serghei. 2025. The Correlation Between Listening Strategies Utilized by University Students in Listening Class and Students Listening Comprehension : a Study of English Department Student at English Study Program of Unmul. Thesis English Department, Faculty of Teacher Training and Education, Mulawarman University, Samarinda. Advisors: (1) Dr. Iwan Setiawan, M.Pd (2) Dr. Desy Rusmawaty, MA Listening strategies are a method that provide aid and assistance for learners and teachers to obtain and comprehend more information and knowledge during the learning process. This study aimed: (1) To identify listening strategies utilized by English Department Students during an English listening class at Mulawarman University English Department (2) To Identify of English department students' listening level at Mulawarman University English Department. (3) To Identify the correlation between listening strategies and listening comprehension. This study used quantitative research design by using questionnaire as instrument to obtain important data. The participants of this study were English Department students at Mulawarman University that were picked purposively by certain criteria. The result of this study indicated that all of the Selected participants from English department had utilized and applied three given listening strategies which were metacognitive, cognitive and socio-affective with cognitive strategy came as the most dominant method used during listening courses with 40% in the 7th semester, 45% in the 5th semester and 44% in the 3rd semester. Followed by metacognitive as the second most used with 40% in the 7th semester, 36% in the 5th semester and 35% in the 3rd semester. Socio affective as the least preferred strategy with 20% percentage in the 7th semester, 19% in the 5th semester and 21% in the 3rd semester. The result of this study also showed that the listening level of English department students of mulawarman university were at the good level of listening level classification with the score of 76.34. This finding indicates that these students in this level were capable of comprehending spoken language in general and have a moderate level of understanding. Lastly, this research also showed that there was a positive correlation between listening strategy and students’ listening comprehension with a value of (0.496) and the p-value of <0.001. The results indicated that the higher the application of listening strategy during listening course, the higher students’ comprehension level. It showed that listening strategies correlate with listening comprehension.